Methylmethacrylic Ball Interpositional Arthroplasty in Ankylosis of Temporomandibular Joint-A Case Report - P. K. Bilwani (Indian Journal of Plastic Surgery, 1976)
A case of unilateral temporo mandibular joint ankylosis following middle ear infection is presented.